4x+5-2x=3+x-12

Simple and best practice solution for 4x+5-2x=3+x-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+5-2x=3+x-12 equation:


Simplifying
4x + 5 + -2x = 3 + x + -12

Reorder the terms:
5 + 4x + -2x = 3 + x + -12

Combine like terms: 4x + -2x = 2x
5 + 2x = 3 + x + -12

Reorder the terms:
5 + 2x = 3 + -12 + x

Combine like terms: 3 + -12 = -9
5 + 2x = -9 + x

Solving
5 + 2x = -9 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
5 + 2x + -1x = -9 + x + -1x

Combine like terms: 2x + -1x = 1x
5 + 1x = -9 + x + -1x

Combine like terms: x + -1x = 0
5 + 1x = -9 + 0
5 + 1x = -9

Add '-5' to each side of the equation.
5 + -5 + 1x = -9 + -5

Combine like terms: 5 + -5 = 0
0 + 1x = -9 + -5
1x = -9 + -5

Combine like terms: -9 + -5 = -14
1x = -14

Divide each side by '1'.
x = -14

Simplifying
x = -14

See similar equations:

| 18-3(8x+4)=-6(4x-1) | | -7-8m=145 | | 1+32=-5(7x-7) | | -0.813+x=-1.096 | | (3x-4y)(7x-4y)= | | x+31=90 | | 4x+7(3x-13)=184 | | 19-3n=8(6n-8) | | 2x+2(3x+8)=-56 | | 4x+14=3x-1 | | x(x-3)+4x-3=8x+x(x+3) | | 2x^3-3x-2=0 | | x+31+x=5x-22 | | 2x-15=-3+5 | | 3x+4(3x-5)-10=0 | | y=5+x+4x^2 | | -15-4x=34+3x | | 7x+2y=50 | | 85-5x+70+10x=180 | | 3p+7=11+2p | | a-25=(-5) | | 42x+5=83 | | 3T-32=0 | | (xD^4+D^3)y=0 | | 4x^4+7x^2-6=0 | | x(x+1)=x^2+5 | | 6(5x-3)=36x | | 5x-(2)=2x+13 | | 1.0t+6.34t-2.12t= | | 4x-13=33 | | -21=k+9 | | c=(-20)+(-8) |

Equations solver categories